Prevalence of Myopia amongst patients with refractive error in the Kumasi Metropolis of Ghana (Journal of Science and Technology, 2016)
This paper sought to report on the prevalence of myopia and its distribution pattern among individuals who seek eye health in eye care facilities in Kumasi. In a retrospective cross sectional study, the two leading major public eye facilities (Komfo Anokye Teaching Hospital and Kumasi South hospital) were purposively selected whilst simple random sampling method was used to select five of the private eye care facilities. In total, 6027 records of subjects with refractive errors who visited the eye facilities between January 2010 and December 2010 were reviewed. The results revealed that 54.12% of the patients records reviewed were myopic. Of the 3263 myopes, 75.45% were low myopes, 15.78% were moderate myopes and 8.77% were high myopes. The prevalence of myopia among the male study population was 58.68% and 50.31% among the female subjects. The study concludes that myopia is the most common refractive error that is presented for refraction in the eye facilities in Kumasi. More community based studies are required to determine the actual burden of myopia and to explore the gender bias in the larger population